Tata Kelola Pembentukan Karakter Siswa di Madrasah Kota Magelang - Sofia Nur; Purwanto Purwanto; Rochmat Budi Santoso (ITB AAS INDONESIA Surakarta, 2021)
This study aims to describe governance in the formation of the character of madrasah students in Magelang City in 2021, to describe student responses to the governance of student character building by madrasas in Magelang City in 2021, and to describe the evaluation of governance in character building of madrasah students in Magelang City which including Madrasah Ibtidaiyah, Madrasah Tsanawiyah, and Madrasah Aliyah. This study used descriptive qualitative method. This method is used to describe and explain madrasa management in shaping the character of students in madrasas in the Magelang region. The places chosen to conduct the research were Madrasah Ibtidaiyah, Madrasah Tsanawiyah, Madrasah Aliyah. Madrasah Ibtidaiyah (MI) includes MI Muhammadiyah Terpadu Harapan Magelang City and MI Al Iman City Magelang. Madrasah Tsanawiyah (MTs) include MTsN 1 Magelang City and MTsN 2 Magelang City. Madrasah Aliyah (MA) includes MAN of Magelang City and MA Al Iman of Magelang City. Data collection techniques in this research are using content/document analysis techniques, in-depth interviews, and events/observations. The method used to check the validity of the data is the triangulation method. The results showed that: 1). Governance in shaping the character of madrasa students in Magelang City in 2021 is generally carried out by the madrasah through various habituation and extracurricular activities as well as positive self-development such as reading Asmaul Husna, Tahfidzul Qur'an, Tilawatil Qur'an, Sunnah fasting and others. has gone well; 2). Student responses to the management of student character building by madrasas in Magelang City are generally very good and positive, students carry out various activities implemented by the school enthusiastically and consistently; 3). The evaluation carried out for the formation of student character applied to madrasas in Magelang City was successful and as expected because in general the students had good morals and carried out various positive activities both within the madrasa and outside the madrasa environment.